Early Career Outcomes of International Bachelor’s Degree Recipients from U.S. Institutions: The Role of International Status and Region of Origin - Jiang, Xiushan (Journal of International Students, 2018)
Based on neo-racism theory and human capital theory, this study examined whether international bachelor’s degree recipients who graduated from U.S. institutions have significant early career outcome differences compared to domestic bachelor’s degree recipients in terms of major-job match, annual earnings, and job satisfaction. Recognizing the significant differences in language, culture, and socio-economic conditions among immigrants from different countries of origin, this study further explored possible differences in career outcomes of international bachelor’s degree recipients by regions of origin. The findings of this study suggest that international degree recipients have gained labor market parity in majorjob match as well as salary and job satisfaction with their domestic counterparts, all things being equal. Further, this study found evidence that region of origin plays an important role in shaping international bachelor’s degree recipients’ major-job match and annual earnings. The policy implications for postsecondary institutions and the U.S. as a society are discussed.